Communicating change: a multimodal critical discourse analysis of China’s poverty reduction posters - Liu, Wenyu; Du, Chengcheng; Liu, Fengguang (Frontiers in Communication, 2024)
This study conducts a Multimodal Critical Discourse Analysis guided content analysis of 56 Chinese government-sponsored poverty reduction posters across three historical stages since the founding of the People’s Republic of China to understand visual strategies, represented participants, and thematic shifts. Initially, visual strategies focus on action-oriented, collective agricultural activities. Over time, they shift to highlighting technological advancements and individual achievements, using “offer” images and various perspectives to engage viewers. Early posters predominantly feature peasants and collective groups, later expanding to include individuals and technological symbols, reflecting China’s socio-economic reforms. The thematic shifts move from collective efforts to targeted, locally-tailored strategies and the principle of “teaching people to fish,” mirroring broader socio-political transformations. This evolution underscores the role of visual media in shaping public understanding and garnering support for national policies. By highlighting the dynamic interaction between visual elements and socio-political contexts, the study reveals how government-sponsored media has adapted to effectively communicate the progress and objectives of China’s poverty elimination efforts.